Tinjauan yuridis terhadap sistem alih daya (outsourcing) pada pekerja di Indonesia - Suyoko Suyoko; Mohammad Ghufron AZ (University of Merdeka Malang, 2021)
The practice of outsourcing at this time is increasingly being carried out by both entrepreneurs and outsourcing service providers themselves. Along with the development of industrial labor relations with an outsourcing system, it creates many negative things for the development of workers / laborers. Many workers' rights are neglected by companies that use outsourcing services. The issues raised are how the regulation regarding the outsourcing system for workers in Indonesia and how legal protection for outsourcing workers in Indonesia. The results of this research are that the regulations regarding the outsourcing system in Indonesia are contained in Article 64 to Article 66 of the Manpower Act, where in 2020 after the issuance of Law Number 11 of 2020 concerning Job Creation there are changes regulated in Article 81 numbers 18 to 20. Legal protection for outsourced workers / laborers in the work copyright law is regulated in Article 81 point 20, however until now the implementing regulations of this article have not been issued by the Government.How to cite item: Suyoko., Ghufron AZ, M. (2020).Tinjauan yuridis terhadap sistem alih daya (outsourcing) pada pekerja di Indonesia. Jurnal Cakrawala Hukum, 12(1). 99-109.doi:10.26905/idjch.v12i1.5780.